Research status of application of quality of life assessment scale and symptom severity evaluation scale for patients with fecal incontinence - Wang Miao; Wu Xuxiong; Shi Rong; Huang Juan; Chen Yunong (结直肠肛门外科)
Fecal incontinence symptoms have caused varying degrees of impact on patients’ lives and social interactions. Scales have important application value for such patients, helping to understand the patient’s condition and perception more comprehensively. This article reviews the current research status of the application of relevant scales in patients with fecal incontinence from the perspectives of quality of life assessment scale and symptom severity evaluation scale by combining with literature data.